Macroporous silicon dioxide composite carrier as well as preparation method and application thereof
By preparing a macroporous silica composite support composed of SiO2 and Al2O3, the problem of carbon accumulation in the existing support in the liquid phase hydrogenation catalyst is solved, and higher catalytic activity and longer service life are achieved.
Patent Information
- Application Number
- CN202310987244.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-18
Smart Images

Figure BDA0004382508100000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and more specifically, to a method for preparing a macroporous silica composite carrier, a macroporous silica composite carrier prepared by the method, and application of the macroporous silica composite carrier in catalyst preparation. Background Art
[0002] Silica porous materials have good chemical and thermal stability, high specific surface area, orderly and adjustable pore structure, strong fluidity and easy loading. Therefore, they are widely used in catalytic degradation, environmental energy, biomedicine and other fields.
[0003] In the field of catalytic technology, silica is often used as a carrier in the preparation of hydrogenation catalysts due to its good chemical stability and high specific surface area. During the preparation process, silica needs to be extruded and then loaded with active metals to obtain a molded catalyst. During the molding process of silica, the size and structure of its pores have a crucial influence on the activity of the catalyst.
[0004] The silica particles are small and dense, and the processed silica carrier has a large specific surface area but a small pore volume and pore size. The inventors of the present invention have found that in practical applications, especially in long-term industrial applications of liquid phase hydrogenation, the pore structure of the catalyst will be blocked by carbon deposition, which is not conducive to the diffusion of materials on the surface and inside of the catalyst, thereby reducing the catalytic activity and affecting the service life of the catalyst.
[0005] Therefore, it is of practical significance to develop a new macroporous carrier to meet the needs of liquid phase hydrogenation production. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a macroporous silica composite carrier and a preparation method and use thereof. The macroporous silica composite carrier of the present invention has a larger pore volume and pore diameter, and the catalyst prepared using the macroporous silica composite carrier has a longer service life.
[0007] The first aspect of the present invention is to provide a silica composite carrier containing SiO2 and Al2O3, wherein the content of SiO2 is 65-90wt% based on the total weight of SiO2 and Al2O3 as 100wt%; wherein the average pore size of the silica composite carrier is 7.6-9.4nm.
[0008] According to the present invention, based on the total weight of SiO2 and Al2O3 as 100wt%, the content of SiO2 is 65-90wt%. In a preferred embodiment of the present invention, based on the total weight of SiO2 and Al2O3 as 100wt%, the content of SiO2 is 70-85wt%, for example, 70, 75, 80, 85wt%, and any two values or any interval between any two values.
[0009] According to the present invention, preferably, based on the total weight of the silica composite carrier, the silica composite carrier comprises 65-90wt% SiO2 and 10-35wt% Al2O3, and more preferably, the composite carrier comprises: 70-85wt% SiO2 and 15-30wt% Al2O3.
[0010] According to the present invention, the average pore size of the silica composite carrier is 7.6-9.4 nm. In a preferred embodiment of the present invention, the average pore size of the silica composite carrier is 8-9.3 nm, such as 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.1, 9.2, 9.3 nm, and any two values or any interval between any two values.
[0011] According to the present invention, the specific surface area of the silica composite carrier has a wide range. In a preferred embodiment of the present invention, the specific surface area of the silica composite carrier is 120-260 m 2 / g, preferably 150-220m 2 / g.
[0012] According to the present invention, the average pore volume of the silica composite carrier has a wide range. In a preferred embodiment of the present invention, the average pore volume of the silica composite carrier is 0.45-0.9 m 3 / g, preferably 0.7-0.88m 3 / g.
[0013] In a preferred embodiment of the present invention, the silica composite carrier is prepared by the following preparation method, which comprises: kneading, extruding, drying and calcining a mixture containing a silica precursor, an alumina precursor, a binder and an acid solution to obtain a precursor of the composite carrier; soaking the precursor in an alkaline solution, washing to remove the alkali, and drying to obtain the silica composite carrier.
[0014] The second aspect of the present invention is to provide a method for preparing the silica composite carrier described in the first aspect, comprising: kneading a mixture containing a silica precursor, an alumina precursor, a binder and an acid solution to obtain a plastic body, and then extruding, drying and calcining to obtain a precursor of the composite carrier; soaking the precursor in an alkaline solution, washing to remove the alkali, and drying to obtain the silica composite carrier.
[0015] In a preferred embodiment of the present invention, the preparation method comprises the following steps:
[0016] (1) mixing a precursor of silicon dioxide, a precursor of aluminum oxide and a binder to obtain a dry mixed material; adding an acid solution to the dry mixed material and kneading to obtain a plastic body;
[0017] (2) extruding the plastic body to obtain a wet molded body;
[0018] (3) drying and calcining the wet molded body to obtain a carrier precursor;
[0019] (4) Soaking the carrier precursor in an alkaline solution, washing it to neutrality, and drying it to obtain the silica composite carrier.
[0020] According to the present invention, the precursor of silica can be selected from a wide range. In a preferred embodiment of the present invention, the precursor of silica is at least one of silica powder, acidic silica sol and alkaline silica sol; preferably silica powder.
[0021] According to the present invention, the precursor of aluminum oxide can be selected from a wide range. In a preferred embodiment of the present invention, the precursor of aluminum oxide is at least one of pseudo-boehmite, aluminum hydroxide and aluminum sol; preferably pseudo-boehmite.
[0022] According to the present invention, the binder can be selected from a wide range. In a preferred embodiment of the present invention, the binder is at least one of sesbania powder, methyl cellulose and soluble starch; preferably methyl cellulose.
[0023] According to the present invention, the amount of each raw material can be selected within a wide range. In a preferred embodiment of the present invention, based on the total weight of the plastic body as 100wt%, the amount of the silicon dioxide precursor is 25-45wt%, preferably 27-42wt%, the amount of the aluminum oxide precursor is 5-30wt%, preferably 6-26wt%, the amount of the binder is 1-2wt%, preferably 1.2-1.7wt%, and the amount of the acid solution is 44-60wt%, preferably 45.8-50.3wt%.
[0024] More preferably, based on the total weight of the plastic body as 100wt%, the amount of the silicon dioxide precursor is 31-38wt%, the amount of the aluminum oxide precursor is 10.6-22wt%, the amount of the binder is 1.2-1.4wt%, and the amount of the acid solution is 45.8-50wt%.
[0025] According to the present invention, the acid in the acid solution can be selected from a wide range. In a preferred embodiment of the present invention, the acid in the acid solution is at least one of nitric acid, sulfuric acid, hydrochloric acid and phosphoric acid, preferably nitric acid.
[0026] According to the present invention, the mass concentration of the acid solution can be selected within a wide range. In a preferred embodiment of the present invention, the mass concentration of the acid solution is 1-9wt%, such as 1, 3, 6, 9wt%, and any two values or any interval between any two values.
[0027] In a preferred embodiment of the present invention, in step (3):
[0028] The drying is carried out in the following order:
[0029] a. First dry in air at 20-35℃ for 1-3 hours;
[0030] b. Then dry in air at 70-90℃ for 2-4 hours;
[0031] c. Finally, dry in air at 110-130℃ for 12-16 hours.
[0032] In a preferred embodiment of the present invention, the calcination conditions include: the calcination temperature is 300-600°C, and the calcination time is 3-5 hours. Preferably, the heating rate is 2-6°C / min, the calcination temperature is 300-600°C, and the calcination time is 3-5 hours.
[0033] According to the present invention, the alkali in the alkaline solution can be selected from a wide range. In a preferred embodiment of the present invention, in step (4), the alkali in the alkaline solution is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate and sodium bicarbonate, preferably sodium hydroxide.
[0034] According to the present invention, the mass concentration of the alkaline solution can be selected within a wide range. In a preferred embodiment of the present invention, the mass concentration of the alkaline solution is 0.5-5%, more preferably 1%-2%.
[0035] According to the present invention, the amount of the alkaline solution can be selected within a wide range. In a preferred embodiment of the present invention, the mass ratio of the alkaline solution to the carrier precursor is not less than 1.25.
[0036] According to the present invention, the soaking time of the alkaline solution can be selected within a wide range. In a preferred embodiment of the present invention, the soaking time of the alkaline solution is 2-6 hours.
[0037] In a preferred embodiment of the present invention, the drying is carried out in the following order: step a-step b:
[0038] a. Dry in air at 60-80℃ for 12-24 hours;
[0039] b. Then dry in air at 110-130℃ for 4-8 hours.
[0040] In the present invention, for example, the following technical scheme can be specifically used to prepare the macroporous silica composite carrier of the present invention:
[0041] (1) according to the mass ratio of each raw material for preparing the carrier, weighing silicon dioxide powder, pseudo-boehmite and methyl cellulose, mixing them evenly to obtain a dry mixed material; adding an acid solution to the dry mixed material, kneading, and obtaining a plastic body;
[0042] (2) extruding the plastic body to obtain a wet molded body;
[0043] (3) Dry in air at 20-35°C for 1-3 hours; in air at 70-90°C for 2-4 hours; in air at 110-130°C for 12-16 hours;
[0044] (4) heating at a rate of 2-6°C / min, calcining at a temperature of 300-600°C for 3-5 hours to obtain a carrier precursor;
[0045] (5) After soaking the carrier precursor in an alkaline solution for 2-6 hours, washing with deionized water until the washing solution is neutral;
[0046] (6) Drying in air at 60-80° C. for 12-24 hours; drying in air at 110-130° C. for 4-8 hours to obtain a macroporous silica composite carrier.
[0047] The third aspect of the present invention is to provide a use of the silica composite carrier described in the first aspect or the silica composite carrier prepared by the preparation method described in the second aspect in a catalyst.
[0048] Preferably, the catalyst is a liquid phase hydrogenation catalyst.
[0049] As described above, the present invention kneads a mixture of a precursor of silica, a precursor of alumina, a binder and an acid solution to obtain a plastic body, and then extrudes, dries and calcines to obtain a precursor of the composite carrier; the precursor is soaked in an alkaline solution, washed to remove the alkali, and dried to obtain the silica composite carrier. The silica composite carrier contains SiO2 and Al2O3, and the content of SiO2 is 65-90wt% based on the total weight of SiO2 and Al2O3 as 100wt%; the average pore size of the silica composite carrier is 7.6-9.4nm. The silica composite carrier of the present invention has a larger pore size and pore volume, and the catalyst prepared using the silica composite carrier of the present invention has good catalytic performance and a longer catalyst service life.
[0050] The inventors of the present invention believe that the reason for the above advantages is that: the present invention adopts a precursor of silicon dioxide and a precursor of aluminum oxide, preferably adopts a preferred ratio scheme for preparing a plastic body, and obtains a precursor of the composite carrier through processes such as roasting. The precursor is then immersed in an alkaline solution to wash away part of the Al and increase the pore size of the catalyst. The silica composite carrier of the present invention has a larger pore volume. In application, the silica composite carrier of the present invention can improve the diffusion efficiency of materials on the surface and inside of the catalyst, reduce carbon deposition, increase reaction activity, and improve service life.
[0051] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) The macroporous silica composite carrier of the present invention has a large pore volume and pore diameter and can be directly used for the preparation of catalysts.
[0053] (2) The catalyst prepared using the macroporous silica composite carrier of the present invention has good catalytic performance and a longer catalyst service life.
[0054] (3) The preparation process of the macroporous silica composite carrier of the present invention is simple, low-cost, and has extremely high industrial application and promotion value. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0056] The raw materials used in the following examples and comparative examples are all commercially available.
[0057] The average particle size of the silicon dioxide powder used in the following examples and comparative examples is 800 mesh.
[0058] The pseudo-boehmite used in the following examples and comparative examples contains 70% Al2O3.
[0059] In the following embodiments and comparative examples:
[0060] The specific surface area, average pore volume and average pore diameter of the carrier were determined using the ASAP 2020M+C fully automated chemical adsorption analyzer produced by MICROMERITICS Corporation of the United States.
[0061] Example 1
[0062] This example is used to illustrate the silica composite carrier and its preparation method of the present invention.
[0063] Weigh 78.0g of silica powder, 39.3g of pseudo-boehmite and 3.0g of methyl cellulose in a kneader and mix for 20 minutes to obtain a dry mixture; weigh 120g of a 5% nitric acid aqueous solution, add it to the dry mixture, and knead for 30 minutes to obtain a plastomer. The plastomer is extruded through an extruder to obtain a wet molded body. The wet molded body is placed in 25°C air, dried for 2 hours, then placed in 80°C air, dried for 3 hours, and then placed in 120°C air, dried for 14 hours. The dried molded body is placed in a muffle furnace, heated to 450°C at a rate of 4°C / min, roasted for 4 hours, and then cooled naturally to obtain a carrier precursor.
[0064] Weigh 216 g of 2% NaOH aqueous solution, soak the carrier precursor in it, and wash the soaked carrier precursor with deionized water after 4 hours until the washing liquid is neutral. Then, dry the washed carrier precursor in air at 60-80°C for 18 hours; and dry it in air at 110-130°C for 6 hours to obtain a macroporous silica composite carrier S1.
[0065] Based on the total weight of the macroporous silica composite carrier, the carrier S1 contains: SiO2 78%, Al2O3 22%; the specific surface area of the carrier is 157.10 m 2 / g, average pore volume is 0.858m 3 / g, and the average pore size is 9.217nm.
[0066] Example 2
[0067] The carrier was prepared by the same method as in Example 1, except that the amount of the raw materials used was different. The rest was the same as in Example 1, and a macroporous silica composite carrier S2 was prepared.
[0068] The raw materials used in Example 2 are 70.0 g of silicon dioxide powder, 53.5 g of pseudo-boehmite and 3.0 g of methyl cellulose, as well as 120 g of 5% by mass aqueous nitric acid solution and 294 g of 2% by mass aqueous NaOH solution.
[0069] Based on the total weight of the macroporous silica composite carrier, the carrier S2 contains: SiO2 70%, Al2O3 30%; the specific surface area of the carrier is 171.23 m 2 / g, average pore volume is 0.819m 3 / g, and the average pore size is 9.044nm.
[0070] Example 3
[0071] The carrier was prepared by the same method as in Example 1, except that the amount of the raw materials used was different. The rest was the same as in Example 1, and a macroporous silica composite carrier S3 was prepared.
[0072] The raw materials used in Example 3 are 85.0 g of silicon dioxide powder, 26.78 g of pseudo-boehmite and 3.0 g of methyl cellulose, as well as 110 g of 5% by mass aqueous nitric acid solution and 147 g of 2% by mass NaOH aqueous solution.
[0073] Based on the total weight of the macroporous silica composite carrier, the carrier S3 contains: SiO2 85%, Al2O3 15%; the specific surface area of the carrier is 175.94 m 2 / g, average pore volume is 0.804m 3 / g, and the average pore size is 8.965nm.
[0074] Example 4
[0075] The carrier was prepared by the same method as in Example 1, except that the amount of the raw materials used was different. The rest was the same as in Example 1, and a macroporous silica composite carrier S4 was prepared.
[0076] The raw materials used in Example 4 are 85.0 g of silicon dioxide powder, 62.5 g of pseudo-boehmite and 4.0 g of methyl cellulose, as well as 150 g of 5% by mass aqueous nitric acid solution and 343 g of 2% by mass NaOH aqueous solution.
[0077] Based on the total weight of the macroporous silica composite carrier, the carrier S4 contains: SiO2 65%, Al2O3 35%; the specific surface area of the carrier is 204.83 m 2 / g, average pore volume is 0.735m 3 / g, and the average pore size is 8.523nm.
[0078] Example 5
[0079] The carrier was prepared by the same method as in Example 1, except that the amount of the raw materials used was different. The rest was the same as in Example 1, and a macroporous silica composite carrier S5 was prepared.
[0080] The raw materials used in Example 5 are 90 g of silicon dioxide powder, 17.8 g of pseudo-boehmite and 3.0 g of methyl cellulose, as well as 110 g of 5% by mass aqueous nitric acid solution and 196 g of 1% by mass NaOH aqueous solution.
[0081] Based on the total weight of the macroporous silica composite carrier, the carrier S5 contains: SiO2 90%, Al2O3 10%; the carrier specific surface area is 219.79 m 2 / g, and the average pore volume is 0.729m 3 / g, and the average pore size is 8.370nm.
[0082] Comparative Example 1
[0083] This comparative example is used to illustrate a reference silica carrier and its preparation method.
[0084] Weigh 78.0g of silica powder, 31.4g of pseudo-boehmite and 2.5g of methyl cellulose in a kneader and mix for 20 minutes to obtain a dry mixture; weigh 100g of a 5% nitric acid aqueous solution, add it to the dry mixture, and knead for 30 minutes to obtain a plastomer. The plastomer is extruded through an extruder to obtain a wet molded body. The wet molded body is placed in 25°C air, dried for 2 hours, then placed in 80°C air, dried for 3 hours, and then placed in 120°C air, dried for 14 hours. The dried molded body is placed in a muffle furnace, heated to 450°C at a rate of 4°C / min, calcined for 4 hours, and then cooled naturally to obtain a silica composite carrier CS1.
[0085] Based on the total weight of the silica composite carrier, the carrier CS1 contains: SiO2 78%, Al2O3 22%; the specific surface area of the carrier is 247.67 m 2 / g, and the average pore volume is 0.618m 3 / g, and the average pore size is 5.489nm.
[0086] Comparative Example 2
[0087] Weigh 60.0g of silica powder, 71.43g of pseudo-boehmite and 3.0g of methyl cellulose in a kneader and mix for 20 minutes to obtain a dry mixture; weigh 130g of 5% nitric acid aqueous solution, add it to the dry mixture, knead for 30 minutes to obtain a plastomer. The plastomer is extruded through an extruder to obtain a wet molded body. The wet molded body is placed in 25°C air, dried for 2 hours, then placed in 80°C air, dried for 3 hours, and then placed in 120°C air, dried for 14 hours. The dried molded body is placed in a muffle furnace, heated to 450°C at a rate of 4°C / min, roasted for 4 hours, and then cooled naturally to obtain a carrier precursor.
[0088] Weigh 392g of 2% NaOH aqueous solution, soak the carrier precursor in it, and wash the soaked carrier precursor with deionized water after 4 hours until the washing liquid is neutral. Then, dry the washed carrier precursor in air at 60-80°C for 18 hours; dry it in air at 110-130°C for 6 hours to obtain a macroporous silica composite carrier CS2.
[0089] Based on the total weight of the macroporous silica composite carrier, the carrier CS2 contains: SiO2 60%, Al2O3 40%; the specific surface area of the carrier is 143.52 m 2 / g, and the average pore volume is 0.929m 3 / g, and the average pore size is 9.713nm.
[0090] Test Case
[0091] This test example is used to evaluate the catalytic performance of the liquid phase hydrogenation catalyst prepared using the carrier prepared above. The preparation steps of the catalyst are as follows:
[0092] (1) Weigh 10.0 g of the macroporous silica composite carrier, soak it in deionized water for 30 min, drain the water, weigh it, and calculate the water absorption rate of the carrier; where water absorption rate = (carrier mass after water absorption - carrier mass) / carrier mass;
[0093] (2) weighing an appropriate amount of nickel nitrate and dissolving it in deionized water to obtain a nickel nitrate solution;
[0094] (3) The support was added to the nickel nitrate solution, impregnated with equal volumes according to the water absorption rate of the support, and then dried at 120°C for 12 hours, heated to 550°C at a rate of 3°C / min, calcined for 4 hours, and then cooled naturally to obtain a catalyst (the nickel content of each catalyst was 18wt%).
[0095] The macroporous silica composite supports S1-S5 and silica supports CS1, CS2 prepared in the above examples and comparative examples were respectively used to prepare the corresponding catalysts SC1-SC5 and CSC1, CSC2 by the above method.
[0096] The catalyst was applied to the reaction of preparing succinic anhydride by hydrogenation of maleic anhydride, and the activity was evaluated:
[0097] (1) In a stainless steel fixed bed reactor, the catalysts prepared in the above examples and comparative examples were activated by reducing them with a nitrogen-hydrogen mixture at 400° C. for 6 h to obtain an activated catalyst;
[0098] (2) In the presence of the activated catalyst, hydrogen and maleic anhydride are contacted and reacted, and the liquid hourly space velocity of maleic anhydride is 0.25h -1 The molar ratio of hydrogen to maleic anhydride is 15:1, and the contact reaction conditions include: reaction temperature 60°C, pressure 2.0MPa;
[0099] (3) The product after the reaction in step (2) was condensed to obtain a liquid product. The conversion rate of maleic anhydride and the selectivity of succinic anhydride under the catalytic action of the catalysts prepared in each embodiment and comparative example were tested. The specific results are shown in Table 1.
[0100] Wherein, the maleic anhydride conversion rate and the succinic anhydride selectivity are calculated by the following formula:
[0101] (1) Maleic anhydride conversion = (Mo-Ma) / Mo×100%
[0102] (2) Selectivity of succinic anhydride = Mi / (Mo-Ma) × 100%
[0103] Wherein, Mo is the amount of maleic anhydride as raw material, mol; Ma is the amount of maleic anhydride remaining after the reaction, mol; Mi is the amount of succinic anhydride generated after the reaction, mol.
[0104] Table 1
[0105]
[0106] During use, the catalyst has a stable conversion rate for the target raw material and a stable selectivity for the target product. The longer it can maintain the same conversion rate and the same selectivity, the longer the life of the catalyst.
[0107] The water absorption rate of the carrier in Table 1 refers to the water absorption rate of the macroporous silica composite carriers S1-S5 prepared in Examples 1-5 and the silica composite carriers CS1 and CS2 prepared in Comparative Examples 1 and 2.
[0108] It can be seen from the above results that the catalyst prepared by the macroporous silica composite carrier provided by the present invention has high activity and selectivity, can be used for the reaction of hydrogenating maleic anhydride to produce succinic anhydride, and has a high maleic anhydride conversion rate and succinic anhydride selectivity.
[0109] As described above, except for having different carriers, catalysts SC1-SC5 and catalysts CSC1 and CSC2 were obtained under the same preparation conditions as the others. It can be seen that compared with catalysts CSC1 and CSC2, catalysts SC1-SC5 corresponding to the embodiments of the present invention not only have higher maleic anhydride conversion rate and succinic anhydride selectivity, but also have longer catalyst life, and have achieved unexpected technical effects, indicating that the silica composite carrier of the present invention has achieved unexpected technical effects and has made significant progress.
[0110] It can be seen from Examples 1-3 within the preferred range of the present invention that the catalyst corresponding to the silica composite support under the further preferred SiO2 content and Al2O3 content of the present invention and the further preferred average pore size conditions of the silica composite support has a further higher maleic anhydride conversion rate and succinic anhydride selectivity, and also has a further longer catalyst life, indicating that the preferred silica composite support of the present invention has further achieved unexpected technical effects and has more significant progress.
[0111] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
[0112] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0113] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0114] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0115] The endpoints and any values of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0116] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0117] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A silica composite carrier, comprising SiO2 and Al2O3, wherein the content of SiO2 is 65-90wt% based on the total weight of SiO2 and Al2O3 being 100wt%; in, The average pore size of the silica composite carrier is 7.6-9.4 nm.
2. The silica composite carrier according to claim 1, characterized in that: Based on the total weight of SiO2 and Al2O3 being 100wt%, the content of SiO2 is 70-85wt%; and / or, The average pore size of the silica composite carrier is 8-9.3 nm.
3. The silica composite carrier according to claim 1, characterized in that: The specific surface area of the silica composite carrier is 120-260m 2 / g, preferably 150-220m 2 / g; and / or, The average pore volume of the silica composite carrier is 0.45-0.9m 3 / g, preferably 0.7-0.88m 3 / g.
4. The silica composite carrier according to any one of claims 1 to 3, characterized in that: The silica composite carrier is prepared by the following preparation method, which comprises: kneading, extruding, drying and calcining a mixture containing a silica precursor, an alumina precursor, a binder and an acid solution to obtain a precursor of the composite carrier; soaking the precursor in an alkaline solution, washing to remove the alkali, and drying to obtain the silica composite carrier.
5. A method for preparing the silicon dioxide composite carrier according to any one of claims 1 to 4, comprising: A mixture containing a precursor of silicon dioxide, a precursor of aluminum oxide, a binder and an acid solution are kneaded to obtain a plastic body, which is then extruded, dried and calcined to obtain a precursor of the composite carrier; the precursor is soaked in an alkaline solution, washed to remove the alkali, and dried to obtain the silicon dioxide composite carrier.
6. The preparation method according to claim 5, characterized in that The preparation method comprises the following steps: (1) mixing a precursor of silicon dioxide, a precursor of aluminum oxide and a binder to obtain a dry mixed material; adding an acid solution to the dry mixed material and kneading to obtain a plastic body; (2) extruding the plastic body to obtain a wet molded body; (3) drying and calcining the wet molded body to obtain a carrier precursor; (4) Soaking the carrier precursor in an alkaline solution, washing it to neutrality, and drying it to obtain the silica composite carrier.
7. The preparation method according to claim 5 or 6, characterized in that: The precursor of silicon dioxide is at least one of silicon dioxide powder, acidic silica sol and alkaline silica sol; preferably silicon dioxide powder; and / or, The precursor of aluminum oxide is at least one of pseudo-boehmite, aluminum hydroxide and aluminum sol; preferably pseudo-boehmite; and / or, The binder is at least one of sesbania powder, methyl cellulose and soluble starch, preferably methyl cellulose.
8. The preparation method according to claim 5 or 6, characterized in that: Based on the total weight of the plastic body as 100wt%, the amount of the silicon dioxide precursor is 25-45wt%, preferably 27-42wt%, the amount of the aluminum oxide precursor is 5-30wt%, preferably 6-26wt%, the amount of the binder is 1-2wt%, preferably 1.2-1.7wt%, and the amount of the acid solution is 44-60wt%, preferably 45.8-50.3wt%; and / or, The acid in the acid solution is at least one of nitric acid, sulfuric acid, hydrochloric acid and phosphoric acid, preferably nitric acid; and / or the mass concentration of the acid solution is 1-9wt%.
9. The preparation method according to claim 6, characterized in that: In step (3): The drying is carried out in the following order: a. First dry in air at 20-35℃ for 1-3 hours; b. Then dry in air at 70-90℃ for 2-4 hours; c. Finally, dry in air at 110-130℃ for 12-16 hours; and / or, The calcination conditions include: a heating rate of 2-6°C / min, a calcination temperature of 300-600°C, and a calcination time of 3-5 hours.
10. The preparation method according to claim 6, characterized in that: In step (4): The alkali in the alkaline solution is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate and sodium bicarbonate, preferably sodium hydroxide; and / or, the mass concentration of the alkaline solution is 0.5-5%; and / or, The immersion time of the alkaline solution is 2-6 hours; and / or, The drying is carried out in the following order: a. Dry in air at 60-80℃ for 12-24 hours; b. Then dry in air at 110-130℃ for 4-8 hours.
11. Use of the silica composite carrier according to any one of claims 1 to 4 or the silica composite carrier prepared by the preparation method according to any one of claims 5 to 10 in a catalyst; preferably, The catalyst is a liquid phase hydrogenation catalyst.
Citation Information
Patent Citations
Silica-alumina composite carrier and method for preparing same
CN101890373A
Catalyst for preparing isoolefin by cracking tertiary alkyl ether, preparation method for catalyst and application of catalyst
CN102527411A
Alkali treatment modification method of alumina carrier as well as preparation method and application of silver catalyst supported by alumina carrier
CN103357436A
Nickel base catalyst
CN103418384A
Hydrogenation catalyst and preparation method thereof
CN103418395A